Pendampingan Pendampingan Guru Dalam Mengembangkan Video Pembelajaran Yang Menarik - Eveline Siregar; Cecep Kustandi; Elfita Rahmi (LPPM Universitas Negeri Jakarta, 2023)
The change in the learning process to hybrid learning has implications for increasing teacher competence in developing learning media that are more in line with the learning model. School students who are Generation Z are quite familiar with the latest technology. However, the competence of teachers related to the development of learning media is still very minimal. The low teacher competence is of course best compared to the need for learning media, so there is a gap in meeting the needs of students in the learning process which results in not achieving learning objectives by students optimally. Assistance in the development of learning videos is one of the efforts to improve teacher competence related to the development of learning media. The mentoring design uses the PIE model which consists of the following activities: 1) Planning; 2) Implementation and, 3) Evaluation. Meanwhile, the Interesting Learning Video Development Guidebook was developed using the Derek Rowntree development model which consists of; 1) The Planning Phase; 2) The Writing Preparation Stage; and 3) The Writing and Editing Stage. The results of the study were that 93% of participants stated that the mentoring material was very useful, 91% stated that they were very satisfied with the whole series of mentoring activities that had been carried out, and 80% of the learning video products produced by participants received a proper assessment to be used as a learning medium. Keywords: learning video, development, guidebook, hybrid learning, project-based learning